Design and development of referrals automation, a SMART on FHIR solution to improve patient access to specialty care. Issue 3 (28th October 2020) - Odisho, Anobel Y; Lui, Hansen; Yerramsetty, Ramakrishna; Bautista, Felicisimo; Gleason, Nathaniel; Martin, Edwin; Young, Jerry J; Blum, Michael; Neinstein, Aaron B
Abstract: Background: Referring patients to specialty care is an inefficient and error-prone process. Gaps in the referral process lead to delays in patients' access to care, negative patient experience, worse health outcomes, and increased operational costs. While implementation of standards-based electronic referral options can alleviate some of these inefficiencies, many referrals to tertiary and quaternary care centers continue to be sent via fax. Objective: We describe the design process and architecture for a software application that has been developed and deployed to optimize the referrals intake process by automating the processing and digitization of incoming specialty referral faxes, extracting key data elements and integrating them into the electronic health record (EHR), and organizing referrals. Methods: A human-centered design approach was used to identify and describe the inefficiencies in the external referral process at our large, urban tertiary care center. Referrals Automation, an application to convert referral faxes to digital referrals in the EHR, was conceptualized based on key stakeholder interviews and time and motion studies. This application was designed using Substitutable Medical Applications and Reusable Technologies (SMART) and Fast Healthcare Interoperability Resource (FHIR) platforms to allow for adaptability into other healthcare organizations. Results: Referrals Automation software was developed as a healthcare information technology solution to streamline the fax to referral process. The application was implemented into several specialty clinics. Metrics were built-in to the applications to evaluate and guide the further iteration of these features. Conclusions: Referrals Automation will enhance the referrals process by further streamlining and organizing the patient referral process.